The “Statistically Average” Early Haliburton Farm: A Case Study from the Kennaway Settlement - Martinello, Christopher (Ontario History)

(untitled) (The Ontario Historical Society, 2015)
Haliburton County, now a major cottage and lumbering area, was founded for the purpose of farming, before the west was officially open for settlement. The original two settlements were Haliburton Village and Kennaway, now a ghost town. Local census and tax assessment registers for Kennaway can tell us who the pioneers were, and exactly what kinds of crops and livestock they tended. This allows us to determine average annual crop yields, livestock numbers, acres of land cleared, and the average family and farm sizes in the region. From this we can construct a “statistically average” early Haliburton farm and discover with precision what some of Ontario’s last pioneer farms were like.